PENGARUH UKURAN BIBIT TERHADAP PEMBENTUKAN BIOMASSA TANAMAN BAWANG MERAH PADA TINGKAT PEMBERIAN PUPUK NITROGEN YANG BERBEDA - Agus Mulyadi Purnawanto (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2013)
This study aims to determine the size of onion seeds and dosage of the most efficient nitrogen fertilizer on plant biomass formation of red onion. The experiment was conducted at the Green House Faculty of Agriculture, University of Muhammadiyah Purwokerto for five months from December 2010 until May 2011, study prepared based on randomized block design and each treatment was repeated four times. This study consists of two factors: First, the size of onion bulbs (U), consisting of tubers with a size of 3 grams (U1) and the size of 5 grams (U2). Second, the dose of fertilizer nitrogen (N), consisting of Nitrogen fertilizer was given as much as 46 kg / ha (N1), Nitrogen fertilizer was given as many as 92 kg / ha (N2) and nitrogen fertilizers were given as much as 138 kg / ha (N3). The results showed that the unfavorable weather factors could lead to yet determine the size of onion seed and nitrogen fertilizer are most efficient for the formation of plant biomass. There was no significant interaction between seed size with a dose of nitrogen fertilizer on the efficiency of biomass formation of onion plants viewed from all variable. Key words : onion, fertilizer, bulb, nitrogen